RENT AGREEMENT - Abdreymov Yusupbay Turdibaevich; Dawletmuratova Nargiza Bakhitbayevna (Ecominds Press, 2025)
This article provides information on the legal concept, content, significance, and practical application of the annuity contract. The types of annuity contracts, namely fixed annuity and lifetime annuity, are revealed in civil law relations. The grounds for concluding and terminating the contract are indicated.
Keywords: Annuity contract, annuity recipient, annuity payer, fixed annuity, lifetime annuity, significance in civil legal relations, annuity contract and its features in the Republic of Uzbekistan.